Gold(I) complexes with eight-membered NHC ligands: synthesis, structures and catalytic activity - Cervantes Reyes, Alejandro; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2020)
A series of expanded-ring NHC gold complexes of the formula (NaphtDHD−Ar)Au−X (NaphtDHD=4,5-dihydro-1H-naphtho[1,8-ef][1,3]diazocin-3(2H)-ylidene; Ar: Mes=2,4,6-trimethylphenyl, Dipp=2,6-diisopropylphenyl or Xyl=2,6-dimethylphenyl; X=Cl, NCCH3, NTf2) have been synthesized, including the first gold(I) triflimidate complex (5) stabilized by an eight-membered NHC ligand. The new organogold compounds have been characterized by mass spectrometry, IR spectroscopy, and 1H and 13C NMR spectroscopy. The structural geometries of 3 b-c and 5 have been unequivocally established by crystallographic analysis revealing broad N-C-N angles (>121°) and high buried volume values (46-54%). The first catalytic studies were carried out on the cycloisomerization of 1,6-enynes, obtaining full conversions (0.5 mol% catalyst loading) and excellent endo/exo selectivity (up to 99:1), and on the gold-catalyzed phenol synthesis. Lastly, the (NaphtDHD-Dipp)Au+ NTf2− species was subjected to a kinetic experiment in the cyclization of a N-propargyl carboxamide to evaluate the efficiency of the pre-formed catalyst (5) and the in situ activated gold complex (3 b+AgNTf2).